Phase I study evaluating the Fc-optimized FLT3 antibody FLYSYN in AML patients with measurable residual disease - Heitmann, Jonas S.; Schlenk, Richard Friedrich; Dörfel, Daniela; Kayser, Sabine; Döhner, Konstanze; Heuser, Michael; Thol, Felicitas; Kapp-Schwoerer, Silke; Labrenz, Jannik; Edelmann, Dominic; Märklin, Melanie; Vogel, Wichard; et al. (Journal of hematology & oncology, 2023)
About half of AML patients achieving complete remission (CR) display measurable residual disease (MRD) and eventually relapse. FLYSYN is an Fc-optimized antibody for eradication of MRD directed to FLT3/CD135, which is abundantly expressed on AML cells. This first-in-human, open-label, single-arm, multicenter trial included AML patients in CR with persisting or increasing MRD and evaluated safety/tolerability, pharmacokinetics and preliminary efficacy of FLYSYN at different dose levels administered intravenously (cohort 1-5: single dose of 0.5 mg/m2, 1.5 mg/m2, 5 mg/m2, 15 mg/m2, 45 mg/m2; cohort 6: 15 mg/m2 on day 1, 15 and 29). Three patients were treated per cohort except for cohorts 4 and 6, which were expanded to nine and ten patients, respectively. Primary objective was safety, and secondary efficacy objective was ≥ 1 log MRD reduction or negativity in bone marrow. Overall, 31 patients were treated, of whom seven patients (22.6%) experienced a transient decrease in neutrophil count (two grade 3, others ≤ grade 2). No infusion-related reaction or dose-limiting toxicity was observed. Adverse events (AEs) were mostly mild to moderate, with the most frequent AEs being hematologic events and laboratory abnormalities. Response per predefined criteria was documented in 35% of patients, and two patients maintained MRD negativity until end of study. Application of 45 mg/m2 FLYSYN as single or cumulative dose achieved objective responses in 46% of patients, whereas 28% responded at lower doses. FLYSYN monotherapy is safe and well-tolerated in AML patients with MRD. Early efficacy data are promising and warrant further evaluation in an up-coming phase II trial. Trial registration This clinical is registered on clinicaltrials.gov (NCT02789254).
Gesehen am 02.04.2024